Aloe vera: Getting Diamond out of Raw Stones - Reddy, P. Rajasekhar (International Journal of Economic Plants, 2017)
This article shares the experiences of the author for developing new entrepreneurs of herbal products manufacturing industry in under developed drought prone district Ananthapuram in Andhra Pradesh. Aloe Vera, a biological resource created by God for saving Humankind from the major ailments, providing nutrition and promoting immunity. Moreover, this plant can grow well in less rainfall area and can withstand drought to some extent. The cultivation of Aloe vera is these areas and establishing processing industry for the upliftment of the poor farmers has been narrated.